Powered Air Purifying Respirator (PAPR) restores the N95 face mask induced cerebral hemodynamic alterations among Healthcare Workers during COVID-19 Outbreak - Bharatendu Chandra; Jonathan Ong; Yihui Goh; Benjamin Yong‐Qiang Tan; Amanda Chan; Jonathan Zhe Ying Tang; Aloysius Sheng‐Ting Leow; Amanda Chin; Kenneth W.X. Sooi; Yi Lin Tan; Chiew S. Hong; Benjamin Zhao Bin Chin; et al. (2020)
Background and aimCOVID-19 pandemic has resulted in an unprecedented increased usage of Personal protective equipment (PPE) by healthcare-workers. PPE usage causes headache in majority of users. We evaluated changes in cerebral hemodynamics among healthcare-workers using PPE.MethodsFrontline healthcare-workers donning PPE at our tertiary center were included. Demographics, co-morbidities and blood-pressure were recorded. Transcranial Doppler (TCD) monitoring of middle cerebral artery was performed with 2-MHz probe. Mean flow velocity (MFV) and pulsatility index (PI) were recorded at baseline, after donning N95 respirator-mask, and after donning powered air-purifying respirator (PAPR), when indicated. End-tidal carbon-dioxide (ET-CO2) pressure was recorded for participants donning PAPR in addition to the N95 respirator-mask.ResultsA total of 154 healthcare-workers (mean age 29 ± 12 years, 67% women) were included. Migraine was the commonest co-morbidity in 38 (25%) individuals while 123 (80%) developed de-novo headache due to N95 mask. Donning of N95 respirator-mask resulted in significant increase in MFV (4.4 ± 10.4 cm/s, p < 0.001) and decrease in PI (0.13 ± 0.12; p < 0.001) while ET-CO2 increased by 3.1 ± 1.2 mmHg (p < 0.001). TCD monitoring in 24 (16%) participants donning PAPR and N95 respirator mask together showed normalization of PI, accompanied by normalization of ET-CO2 values within 5-min. Combined use of N95 respirator-mask and PAPR was more comfortable as compared to N95 respirator-mask alone.ConclusionUse of N95 respirator-mask results in significant alterations in cerebral hemodynamics. However, these effects are mitigated by the use of additional PAPR. We recommend the use of PAPR together with the N95 mask for healthcare-workers doing longer duties in the hospital wards.